Comparison of permanent magnet electric motors used in electric vehicles - OYMAN SERTELLER, NECİBE FÜSUN (My University, 2022)
© 2022 IEEE.Lately, PM (permanent magnet) motors have started to be used frequently due to advantages such as high efficiency, high power density, high torque, lower losses, lower magnet costs, and more effective control with the development of power electronics. PMSM (permanent magnet synchronous motor) types and BLDCM (brushless direct current motor) types, two members of PM motors, have become frequently used motors in electric vehicles (EVs). In this study, PMSM and BLDCM are compared by optimizing magnet thicknesses, structures, and stator winding turn numbers, to improve the efficiency, using ANSYS Maxwell and ANSYS RMxprt software. In the study, surface mount magnet synchronous motor SPMSM with the inner rotor, V-shaped PM inner rotor IPMSM (interior permanent magnet synchronous motor), BLDCM with inner rotor embedded channel mount magnet, BLDCM with inner rotor embedded magnet, BLDCM with inner rotor surface mount magnet and BLDCM with outer rotor are compared.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Algoritmalar; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Control and System Engineering; Signal Processing; Computer Sciences; algorithms; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; ENGINEERING; AUTOMATION & CONTROL SYSTEMS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; Yapay Zeka; Fizik Bilimleri; Elektrik ve Elektronik Mühendisliği; Kontrol ve Optimizasyon; Bilgisayar Bilimi Uygulamaları; Enerji Mühendisliği ve Güç Teknolojisi; Artificial Intelligence; Physical Sciences; Electrical and Electronic Engineering; Control and Optimization; Computer Science Applications; Energy Engineering and Power Technology; BLDCM; channel PM; embedded PM; EV; inner rotor; outer rotor; PMSM; surface PM; EV; surface PM; embedded PM; channel PM; outer rotor; inner rotor; PMSM; BLDCM